Getting Things Done: How to Make Simulation Data FAIR and Ready to Reuse - Müller, Laura; Hinterthaner, Marc; Ortlieb, Eduard; Mohnfeld, Norman; Schultz, Andreas Maximilian; Uhe, Johanna; Koepler, Oliver; Mozgova, Iryna (IFIP Advances in Information and Communication Technology)

Strukturierte FDM-Plattformen: Aktuelle Lösungen und Herausforderungen in Informationsinfrastrukturprojekten - Schultz, Andreas Maximilian; Mozgova, Iryna; Altun, Osman; Karras, Oliver; Koepler, Oliver; Müller, Laura; Nuenberger, Florian; Röwenstrunk, Daniel; Wawer, Max Leo

Quantitative research on SDGs and HRM - Yang, Philip (The Elgar Companion to Human Resource Management Beyond the Sustainable Development Goals)

Wie Performance Management das Engagement steigern kann - Ehmann, Stefanie; Kampkötter, Patrick; Maier, Patrick; Yang, Philip (Controlling & Management Review)

Data Literacy im Wissenschaftsjournalismus – Facetten journalistischer Datenkompetenz und Fortbildungsbausteine zu deren Schulung - Binder, Karin; Vogel, Markus

Simulationsbasiert Signifikanztests verstehen - Rößner, Michael; Binder, Karin; Ufer, Stefan

Boundedness of the Cherednik kernel and its limit transition from type BC to type A - Brennecken, Dominik (Indagationes Mathematicae)

Application of distributed fiber optic sensing for defect detection in adhesive bonds - Hermelingmeier, Lucas; Teutenberg, Dominik; Meschut, Gerson

Single-step self-punching lockbolt process and equipment development for pre-hole-free joining of aluminum sheets using a dual-die system - Böhm, Yannic; Kappe, Fabian; Han, Daxin; Nordmann, Elmar; Yang, Keke; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)

Entwicklung eines methodischen Ansatzes zur Vermeidung der Spritzerbildung beim Widerstandspunktschweißen durch multiparametrische Prozessanalyse mittels künstlicher Intelligenz - Meschut, Gerson; Yang, Keke; Rethmeier, Michael; El-Sari, Bassel

Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Berücksichtigung des Einflusses fertigungsinduzierter Vorverformungen warmaushärtender Klebstoffe auf die Schwingfestigkeit geklebter Verbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Beule, Felix; Possart, Gunnar; Teutenberg, Dominik; Mergheim, Julia; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Methodenentwicklung zur Ermittlung lokaler Klebschichtzustände innerhalb struktureller Verbindungen - Hermelingmeier, Lucas; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimentelle und numerische Untersuchungen zur Alterung von Klebverbindungen unter zyklischer und hygrothermischer Beanspruchung im Stahl- und Anlagenbau - Neubert, Fynn Lucas; Teutenberg, Dominik; Meschut, Gerson; Rodschei, Maxim; Mergheim, Julia (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

χ-colorable graph states: closed-form expressions and quantum orthogonal arrays - Revis, Konstantinos-Rafail; Zakaryan, Hrachya; Raissi, Zahra (Journal of Physics A: Mathematical and Theoretical)
Abstract Graph states are a fundamental class of multipartite entangled quantum states with wide-ranging applications in quantum information and computation. In this work, we develop a systematic approach for constructing and analyzing χ -colorable graph states, deriving explicit closed-form expressions for arbitrary χ . For a broad family of two- and three-colorable graph states, the representations obtained using only local operations require a minimal number of terms in the Z -eigenbasis. We prove that every two-colorable graph state is local Clifford (LC) equivalent to a state expressible as a summation of rows of an orthogonal array (OA). For graph states with χ > 2, we show that they are LC-equivalent to quantum OAs, establishing a direct combinatorial connection between multipartite entanglement and structured quantum states. Furthermore, the upper and lower bounds of the Schmidt measure for graph states with arbitrary χ colorability are discussed, extending the results for an arbitrary local dimension. Our results offer an efficient and practical method for systematically constructing graph states, optimizing their representation in quantum circuits, and identifying structured forms of multipartite entanglement. This approach also connects graph states to k -uniform and absolutely maximally entangled states, motivating further exploration of the structure of entangled states and their applications in quantum networks, quantum error correction, and measurement based quantum computing.

What is and how do we Achieve a Resilient Digital Democracy? - Fuchs, Christian (Open Research Europe)
This paper develops a new concept and framework for understanding resilient digital democracy in an age defined by polarisation, cascading crises, and the global rise of digital authoritarianism. It begins by tracing the concept of resilience from systems theory to social and political life, showing that resilience in democracy is not a mechanical property of systems but a dynamic, human-driven practice grounded in agency, resistance, and collective self-determination. The paper argues that with emerging challenges in the digital sphere, such as misinformation, surveillance capitalism, platform monopolies, deepfakes, and hybrid warfare, democracy can only endure if its digital dimensions are protected and transformed. Building on this foundation, the paper introduces a holistic approach to resilient digital democracy that spans environmental, technological, economic, political, and cultural domains, and advances strategies such as public-commons digital infrastructures, platform co-operatives, public service Internet platforms, free/libre open source software (FLOSS), participatory innovations, and hybrid offline/online democratic practices. The result is a fresh, interdisciplinary vision of how democracy can be reinvented in the digital age.

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Investigation on manufacturing-induced pre-deformation on the fatigue behaviour of clinched joints - Schlichter, Malte Christian; Harabati, Özcan; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
The present study is an experimental analysis of the influence of pre-forming on the failure behaviour of clinched specimens under quasi-static and cyclic loading conditions. In this context, the geometric formation of the clinched joints is taken into account, with regard to the loading behaviour. The study also includes a comparison of the failure behaviour of quasi-static and cyclic tested specimen. Testing is done on non-pre-deformed and pre-deformed specimens. For this purpose, experimental investigations are carried out on two material combinations consisting of HCT590X steel sheet and EN AW-6014 T4 aluminium sheet. The focus is on the fatigue analysis of the clinched joints. The aim is to identify the failure modes under cyclic loading and the crack formation with regard to forming operations prior to the joining process. The investigations show that the cyclic load-bearing behaviour of the HCT590X joints is reduced by introducing a plastic pre-deformation of the to be joined parts.